Dampak Perjanjian ACFTA dan Perlindungan Hukumnya Terhadap Usaha Mikro Kecil Menengah dalam Perdagangan Mainan Anak-Anak di Kota Pekanbaru - Yuni Dhea Utari (Akademika: Jurnal Keagamaan dan Pendidikan, 2020)
The ASEAN-China Free Trade Area (ACFTA) agreement aims to export and import goods with reduced tariffs of up to 0%. Meanwhile, exports and imports can only be carried out by large-scale entrepreneurs. Traders of locally made children's toys are classified as micro, small and medium enterprises and only get the impact of the flood of toys from China due to the ACFTA. The Pekanbaru City Government's obstacles in protecting micro, small and medium scale entrepreneurs in the trade of artificial children's toys in the city against the impact of the ACFTA agreement need special attention. This is due to the government's unpreparedness in responding to ACFTA including unpreparedness in the construction of infrastructure in the form of a market for MSMEs and guidance on how to export and import goods for MSMEs. Constraints also arise from the condition of entrepreneurs who are not open to the world of free markets. There is no unified organization between traders of locally made children's toys to build a joint venture with big entrepreneurs and become producers who are ready to compete with local Chinese products.